Effectiveness of Strength Training in Post Stroke - Shahid, Muhammad; Baig, Uzma Arif; Naseem, Asma (Annals of King Edward Medical University, 2014)
Abstract The study was done to evaluate the effectiveness of strength training in post stroke. This was an experi-mental randomized study, conducted at various Physi-cal Therapy OPD setting areas. Sample n = 30; 3 fem-ales and 12 males as experimental group and 3 females and 12 males as control group were selected through probability sampling. Mean age of 57 with middle re-covery stage of post stroke were included. Different selected strength training exercises were applied on experimental group to assess spasticity, cadence and manual muscle testing. Result was taken by using Mann - Whiteny U test for outcome measures as in ca-dence, spasticity and manual muscle testing. The result of two outcome measure shows significant result whi-ch means the strength training is more effective than the conventional treatment for post stroke of middle recovery stage. Key Words: Post Stroke, spasticity, strength training, conventional treatment.